The Uncertain Mortality Intensity Framework: Pricing and Hedging Unit-Linked Life Insurance Contracts - Jing Li; Alexander Szimayer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
We study the valuation and hedging of unit-linked life insurance contracts in a setting where mortality intensity is governed by a stochastic process. We focus on model risk arising from different specifications for the mortality intensity. To do so we assume that the mortality intensity is almost surely bounded under the statistical measure. Further, we restrict the equivalent martingale measures and apply the same bounds to the mortality intensity under these measures. For this setting we derive upper and lower price bounds for unit-linked life insurance contracts using stochastic control techniques. We also show that the induced hedging strategies indeed produce a dynamic superhedge and subhedge under the statistical measure in the limit when the number of contracts increases. This justifies the bounds for the mortality intensity under the pricing measures. We provide numerical examples investigating fixed-term, endowment insurance contracts and their combinations including various guarantee features. The pricing partial differential equation for the upper and lower price bounds is solved by finite difference methods. For our contracts and choice of parameters the pricing and hedging is fairly robust with respect to misspecification of the mortality intensity. The model risk resulting from the uncertain mortality intensity is of minor importance.
Keywords: G13; G22; C61; 330; unit-linked life insurance contracts; mortality model risk; price bounds; stochastic control; Lebensversicherung; Indexierung; Wertpapieranalyse; Hedging; Versicherungstechnisches Risiko; Sterblichkeit; Stochastischer Prozess; Kontrolltheorie; Theorie